Electrospinning of P3HT-PEO-CdS fibers by solution method and their properties. (April 2017) - Hernández-Martínez, D.; Nicho, M.E.; Hu, Hailin; León-Silva, U.; Arenas-Arrocena, M.C.; García-Escobar, C.H.
Abstract: Homogeneous composite fibers of poly(3-hexylthiophene) (P3HT)-polyethylene oxide (PEO)-Cadmium Sulfide (CdS) were manufactured by electrospinning technique using chloroform as solvent. The incorporation of CdS in the composite fibers was determined by SEM, FTIR and TGA techniques. SEM and confocal microscopy have been used to determine size, surface morphology and distribution of the fluorescence phase in the fibers. A morphology change in P3HT/PEO fibers was caused by the presence of CdS: porous morphology was obtained for low CdS concentration (3.8 wt% and less) and when the content of CdS nanoparticles is higher, they were concentrated at the center of the fibers. The photoluminescence response was modified with CdS inside the P3HT-PEO fibers. By XRD it was determined that the introduction of CdS nanoparticles in the P3HT-PEO fibers caused disorder in P3HT chains. The obtained composite fibers are promising materials for optic and electronic applications.